Mali - Joint World Bank-IMF Debt Sustainability Analysis - World Bank (World Bank, Washington, DC, 2019)
Mali remains at moderate risk of external debt distress. This rating is unchanged from the previous analysis and consistent with the May 2018 Staff Report (IMF Country Report/18/141). All the projected external debt burden indicators remain below their thresholds under the baseline. However, the ratio of the external debt service to exports exceeds its threshold in the case of an extreme shock to exports under a customized scenario that incorporates 2 percentage points of GDP larger fiscal deficits over 2019 to 2023 than the baseline.1 The baseline scenario assumes improved fiscal policies and achievement of the WAEMU fiscal deficit convergence criteria by 2019. As illustrated in the customized scenario, continued shortfall in domestic revenue mobilization and a deterioration in security conditions will result in a weakened fiscal position and increase the likelihood of debt distress. Mali’s main challenge continues to be ensuring macroeconomic stability while protecting social and investment spending and providing for growing security spending and large development needs. To maintain debt at moderate risk rating, it is essential that the authorities continue their efforts to mobilize domestic revenue and implement reforms. Debt management capacity should be strengthened while deepening structural reforms to diversify the exports base.